Abbasid Literature in AL-ADAB JOURNAL: (Rhetorical Studies as an example) - Abdul Reda, Bushra Salam; Hamza, Nasira Ahmed (Al-Adab Journal, 2022)
Contemporary researchers directed their attention to the rhetorical tradition when they realized the necessity of paying attention to the Arabic language and preservation of it, and the desire to accommodate the beauty of literary texts in it, so the books and writings that interest in it appeared The rhetorical sciences, and studies interested in rhetorical issues occupied books of criticism and literature, as well as Journals. Cultural and academic studies issued by universities, including AL-ADAB Journal, rhetorical studies have occupied space .A large number of these studies were classified into two types in terms of the nature of research in these issues, the first of which is: studies theorizing, which is concerned with tracing the emergence of rhetorical sciences and the development of its terminology across literary eras in conjunction with history, and secondly: applied studies that take Arabic poetry in the Abbasid era as a field of application The sciences and arts of rhetoric among the Abbasid poets, and constitute the largest percentage of its predecessor in the Journal, and in the following this research reviews studies including rhetorical issues in Abbasid literature published Al-Adab journal since from its foundation in 1959 to 2010, according to its two categories.